2018
DOI: 10.7554/elife.34864
|View full text |Cite
|
Sign up to set email alerts
|

Gene-specific mechanisms direct glucocorticoid-receptor-driven repression of inflammatory response genes in macrophages

Abstract: The glucocorticoid receptor (GR) potently represses macrophage-elicited inflammation, however, the underlying mechanisms remain obscure. Our genome-wide analysis in mouse macrophages reveals that pro-inflammatory paused genes, activated via global negative elongation factor (NELF) dissociation and RNA Polymerase (Pol)2 release from early elongation arrest, and non-paused genes, induced by de novo Pol2 recruitment, are equally susceptible to acute glucocorticoid repression. Moreover, in both cases the dominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 64 publications
6
69
0
Order By: Relevance
“…demonstrated that large-scale chromatin decompaction in macrophages, which was not dependent on transcription, occurred rapidly upon GR binding and could influence glucocorticoid response over many hours, even when ligand was removed (43). Similarly, in experiments examining GR-mediated repression of proinflammatory genes in mouse macrophages, at least 2 discrete mechanisms were present: (a) promoter accumulation of negative elongation factor (NELF) and (b) blocking of RNA polymerase (Pol) 2 activation (44). It should be noted that these mechanisms, demonstrated in epithelial cells and macrophages, may not be generalizable to ECs, given the exquisite control of GR-mediated responses in specific cell types, a phenomenon that is increasingly recognized.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that large-scale chromatin decompaction in macrophages, which was not dependent on transcription, occurred rapidly upon GR binding and could influence glucocorticoid response over many hours, even when ligand was removed (43). Similarly, in experiments examining GR-mediated repression of proinflammatory genes in mouse macrophages, at least 2 discrete mechanisms were present: (a) promoter accumulation of negative elongation factor (NELF) and (b) blocking of RNA polymerase (Pol) 2 activation (44). It should be noted that these mechanisms, demonstrated in epithelial cells and macrophages, may not be generalizable to ECs, given the exquisite control of GR-mediated responses in specific cell types, a phenomenon that is increasingly recognized.…”
Section: Discussionmentioning
confidence: 99%
“…The glucocorticoid receptor (GR) is typically found, in an inactive state, in the cytoplasm, and, upon ligand binding, it becomes and trans-represses pro-inflammatory genes. This is thought to be substantiated either through direct DNAbinding, by binding a glucocorticoid response element (GRE) or the nuclear factor kappa B (NF-κB) response element (NF κBRE;Meijsing et al, 2009;Surjit et al, 2011;Watson et al, 2013;Weikum et al, 2017;Hudson et al, 2018;Sacta et al, 2018) or 2), or through a DNA independent, direct proteinprotein interaction/crosstalk with other transcription factors, including NF-κB and AP-1 (McEwan et al, 1997;Webster and Cidlowski, 1999;De Bosscher et al, 2003;Liu and Xu, 2012;Trevor and Deshane, 2014). The initial finding of MPA's capability of interfering with the activities of NF-κB or AP-1, at the promoter level, suggested MPA represses cytokineinduced, AP-1 driven genes, as well as NF-κB-driven genes, without impacting the DNA-binding activity of NF-κB, in a GR-dependent manner (Koubovec et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In LPS-stimulated macrophages, GR activation attenuated the recruitment of p300 and histone acetylation, leading to a failure to assemble bromodomain-containing protein 4 coupling the acetylation state with RNA polymerase II elongation and mediator at promoters and enhancers and eventually blocking RNA polymerase II initiation. This histone modification directed GR-driven repression of inflammatory response genes such as IL-1a and IL-1b and cluster of differentiation 83 in LPS-stimulated macrophages (Sacta et al 2018). Therefore, histone deacetylation mediates the inhibitory effect of glucocorticoids on the inflammatory response and guides glucocorticoid signaling-driven adaptation in the cardiac microenvironment during cardiovascular development and disease.…”
Section: Histone Modificationsmentioning
confidence: 98%